2015
DOI: 10.12806/v14/i2/ab2
|View full text |Cite
|
Sign up to set email alerts
|

The Hunger Project: Exercising Civic Leadership with the Community for the Common Good in an Introductory Leadership Course

Abstract: Contemporary trends in leadership education emphasize paradigms of learning and educational practices associated with developing responsible citizens, furthering higher education's civic mission. Yet, few introductory leadership courses include an explicit civic component (Johnson & Woodard, 2014). Service-learning is a high-impact practice designed to link the classroom and community in meaningful ways (Kuh, 2008). This application brief illustrates how Kansas State University faculty, students, and community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Leadership educators have reaffirmed the intersections of community engagement and leadership education for the purpose of developing civic and socially responsible leaders. Community‐engaged learning has been central for some educators, but it has unfortunately remained a peripheral consideration for others (Priest et al, ). The symposium articulates the case for community‐engaged scholarship and teaching as “pedagogy of practice” (Ganz & Lin, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leadership educators have reaffirmed the intersections of community engagement and leadership education for the purpose of developing civic and socially responsible leaders. Community‐engaged learning has been central for some educators, but it has unfortunately remained a peripheral consideration for others (Priest et al, ). The symposium articulates the case for community‐engaged scholarship and teaching as “pedagogy of practice” (Ganz & Lin, ).…”
Section: Resultsmentioning
confidence: 99%
“…The evolving discipline of leadership studies recognizes the necessity of cultivating civic‐mindedness as a fundamental disposition to effective, sustainable 21st century leadership (Priest, Bauer, & Fine, ; Seemiller, ; Wagner & Pigza, ). Community‐engaged learning pedagogies support learners’ exploration of leadership theory and practice, including its more recent social justice orientations, while enabling learners to experience personally how mutuality and reciprocity undergird collaboration across sectors in communities (Wagner & Pigza, ; Waldner, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Service-learning is beneficial to student teachers as it enhances their communication competencies, critical thinking, and compassion (Priest, Bauer & Fine, 2015). It also assists them in guiding their leaners during career selection sessions, comprehending intricate social matters, and on how to relate with wider society and its functionality.…”
Section: Benefits Of Community Service Learning In Teacher Educationmentioning
confidence: 99%
“…Furthermore, research has shown improved institution and society partnerships as a result of adopting service learning (Priest, Bauer & Fine, 2015;Kretzmann & McKnight, 1993 as cited by Van Dijk, Herrington, Crofts, Breunig, Burris, Sullivan & Thomson,2019). Moreover, nearly two-thirds of earlier community-based learners (sixty-four percent) attest that their involvement in community service-learning augmented their enthusiasm for community engagement beyond the completion of the related programs.…”
Section: Benefits Of Community Service Learning In Teacher Educationmentioning
confidence: 99%